HAEMOcare: The First International Epidemiological Study Measuring Burden of Hemophilia in Developing Countries - Gupta, Naresh; Benbouzid, Abderrahmane; Belhani, Meriem; El Andaloussi, Mohammed; Maani, Khadija; Wali, Yasser; Benchikh El Fegoun, Soraya; Saad, Hossam Ali; Mahlangu, Johnny (TH Open, 2019)
Introduction Optimizing hemophilia care remains challenging in developing countries. Burden-of-disease studies are important to develop strategies for improving hemophilia care.Aim The HAEMOcare study evaluated the factors contributing to hemophilia-related orthopedic disease burden in developing countries.Methods HAEMOcare was a noninterventional, cross-sectional, epidemiological study conducted in Algeria, India, Morocco, Oman, and South Africa. Male patients with severe hemophilia (N = 282) aged ≥6 years, without or with inhibitors, being treated on-demand for bleeding were included. Hemophilia-related orthopedic clinical and functional status was assessed using the Hemophilia Joint Health Score (HJHS), radiological status with the Pettersson Score, and quality of life with the EuroQol five-dimension questionnaire (EQ-5D-3L). Direct and indirect economic costs of hemophilia care were also calculated.Results Patients (mean [standard deviation, SD] age: 20.8 [10.6] years) experienced a mean annualized bleeding rate of 25.8. Overall mean (SD) HJHS and Pettersson score were 17.9 (12.8) and 15.0 (13.5), respectively; scores were similar between patients without or with inhibitors (p = 0.21 and 0.76, respectively). Approximately 70% of adults reported problems relating to pain/discomfort and mobility parameters in the EQ-5D-3L. Mean distance to a hemophilia treatment center (HTC) was 79.4 km. As expected, total costs of hemophilia were statistically significantly higher in patients with inhibitors versus without inhibitors (p = 0.002).Conclusion Inadequate access to HTCs and expert care, along with high bleeding rates, led to equivalent hemophilia-related orthopedic morbidity between hemophilia patients without and with inhibitors. HAEMOcare documented the economic and disease burdens associated with suboptimal hemophilia care in developing countries.
Keywords: HAEMOcare; epidemiological study; hemophilia; inhibitors; orthopedic status; quality of life; developing countries